Towards a Typology of Dimensions of the Continuity and Discontinuity of Law: The Perspective of Polish Private Law after the 1989 Transformation - Mańko, Rafał (University of Wroclaw. Faculty of Law, Administration & Economics, 2016)
Discussions concerning the continuity or discontinuity of the legal culture require the elaboration of a rigorous framework, allowing the comparison of hypotheses and findings concerning different periods, legal systems and branches of law. The present paper aims at identifying four fundamental aspects of the possible continuity or discontinuity of law in the positivist sense, therefore only a part of legal culture. The paper proposes four such dimensions: structure, conceptual framework, fundamental principles, institutions and rules. The propositions put forward in the paper are grounded in, and tentatively applied to, Polish private law after the 1989 transformation from state socialism to capitalism.
Keywords: ciągłość prawa; nieciągłość prawa; transformacja społeczno-gospodarcza; struktura prawa; koncepcje prawne; zasady prawne; metody interpretacji; funkcje instytucji prawnych